Evaluasi Pelaksanaan Praktik Oxy-Acetylene Welding di Jurusan Pendidikan Teknik Mesin FT UNY - Arif Marwanto; Riswan Dwi Djatmiko (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectives of this study were: (1) to investigate the implementation of the curriculum (2) to examine the condition of the equipment used in Oxy-Acetylene Welding (OAW) practices 3) to identify problems experienced by the students and the lecturers (4) to determine the students’achievement of OAW practices. This study was categorised into descriptive quantitative. It was explorative with the Context, Input, Process and Product (CIPP) evaluation method. The objects of this study were the students in the course of OAW practices. The data collection techniques were documentation, observation and questionnaires administration. The data was analysed using descriptive analysis. The results showed that the implementation of the OAW practices curriculum was very effective with the mean scores of 93.4%. The problems experienced by the students were resulted from the materials, the equipment, the lecturers, the toolman, the workshop environment, and the jobsheets. Each of them contributed fairly to the problems. The problems consist of low motivation, low safety concerns, inadequate rooms, inadequate equipment and low quantity of practices. The students learning achievement was very good indicated by 60% of the students achieved the good score